Approaches to information-seeking behaviour in psychology: a comparison of early and contemporary studies - Wilson, Thomas D. (Information Research an international electronic journal, 2024)
Introduction. The aim of this paper is to explore the investigation of information-seeking behaviour in the literature of psychology, with special reference to the period before 1981, when the term was introduced into information science, and compare the research of that period, with research reported in 2022-2023. Method. A search of the literature for the term ‘information-seeking behaviour’ was carried out in Web of Science and Scopus for the period 1900 to 1980 and from January 2022 to May 2023, producing two data sets for analysis. Analysis. Descriptive analysis of sources and geographic distribution of the papers is presented. This is followed by an analysis of the research themes and approaches. Results. In the early set of papers the main context of the research was educational and career counselling and the main research perspective social learning theory, with an emphasis on the concept of locus of control. In the later set, the main theoretical interest was in aspects of cognition, with a particular interest in curiosity. Conclusion. There is much that the information science research can learn and apply from the literature of psychology. In particular, social learning theory, cognitive theory, and the associated research instruments could be of value.